Psychological capital and subjective well-being: a multi-mediator analysis among rural older adults - Yujin Sun (BMC Psychology)
Abstract Background Amid global demographic changes, understanding factors associated with subjective well-being among rural older adults has gained prominence. This study investigated the pathways linking psychological capital and subjective well-being, focusing on the mediating roles of subjective socioeconomic status, justice perceptions, and marital satisfaction. Methods Data from the 2017 China General Social Survey were analyzed using a multi-mediation approach. This study examined both the independent and sequential mediating effects of subjective socioeconomic status, justice perceptions, and marital satisfaction in the relationship between psychological capital and subjective well-being. Results The findings identified six significant pathways through which psychological capital is associated with subjective well-being. These pathways demonstrated the independent and sequential roles of subjective socioeconomic status, justice perceptions, and marital satisfaction, thus providing new insights into how these variables are connected in the context of older adults in rural areas. Conclusions This study confirms the positive relationship between psychological capital and subjective well-being among older adults in rural areas. It highlights the importance of subjective socioeconomic status, justice perceptions, and marital satisfaction as key mediators in this relationship. The findings enhance understanding of the mechanisms linking psychological capital and subjective well-being while providing valuable guidance for promoting well-being in rural communities. This study also broadens the research focus on psychological capital and offers promising directions for future studies on rural older adults.